Diabetic Blood Glucose Level Profile with Stratified Dose Streptozotocin (SD-STZ) and Multi Low Dose Streptozotocin (MLD-STZ) Induction Methods - Hikmah, Nuzulul; Shita, Amandia Dewi Permana; Maulana, Hafiedz (Journal of Tropical Life Science, 2015)
The prevalence of diabetes increased from year to year. Diabetic animal model was developed to study the pathogenesis and treatment in diabetes. The aim of this study was to determine the profile of diabetic blood glucose levels using a stratified dose streptozotocin (STZ-SD) and multi-low dose streptozotocin (MLD-STZ) induction methods. 27 Wistar rats were divided into three groups, control group, SD-STZ group, and MLD-STZ group. The induction of experimental animal was using the method of SD-STZ and MLD-STZ for 5 consecutive days intraperitoneally. SD-STZ method using stratified dose of 40, 35, 30, 25, and 20 mg/Kg of body weight, while MLD-STZ method using a dose of 20 mg/Kg of body weight for 5 times. The measurement of blood glucose level (BGL) and body weight (BW) in animal was made on 2, 4, 7, and 14 days after STZ induction. The results of this study indicate that the diabetic conditions (BGL â‰¥ 300 mg/dl) on the SD-STZ induction method was more stable, and no deaths occurred in experimental animals.Keywords: Streptozotocin (STZ), diabetes, blood glucose level (BGL).